1997
DOI: 10.1016/s0925-4439(97)00061-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mtDNA and nDNA encoded respiratory chain proteins in chemically and genetically-derived Rho0 human fibroblasts: a comparison of subunit proteins in normal fibroblasts treated with ethidium bromide and fibroblasts from a patient with mtDNA depletion syndrome

Abstract: Although much progress has been made in identifying genetic defects associated with mitochondrial diseases, the protein expression patterns of most disorders are poorly understood. Here we use immunochemical techniques to describe subunit expression patterns of respiratory chain enzyme complexes II (succinate dehydrogenase: SD) and IV (cytochrome c oxidase: COX) in cultured cells lacking mtDNA (Rho0 cells) derived either chemically by exposure of normal cells to ethidium bromide, or genetically in cells derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 39 publications
7
65
0
6
Order By: Relevance
“…Western blots of mitochondria from MRC5 and GM00028 were probed with an IF 1 -specific monoclonal antibody, together with a mixture of mAbs specific for subunits of the 5 OXPHOS complexes. As previously reported (25,38) this very sensitive method can reveal specific defects in the enzymes of the OXPHOS system. The results in Fig.…”
Section: Humanmentioning
confidence: 55%
See 1 more Smart Citation
“…Western blots of mitochondria from MRC5 and GM00028 were probed with an IF 1 -specific monoclonal antibody, together with a mixture of mAbs specific for subunits of the 5 OXPHOS complexes. As previously reported (25,38) this very sensitive method can reveal specific defects in the enzymes of the OXPHOS system. The results in Fig.…”
Section: Humanmentioning
confidence: 55%
“…All cell cultures were maintained and mitochondria isolated by cell homogenization and differential centrifugation as previously described (25). The mitochondria were suspended in final wash buffer with inhibitors (see above), and protein concentrations were determined by measuring the A 280 of 10 l of mitochondria diluted in 1 ml of 0.6% SDS and heated to 94 -100°C for 4 min.…”
Section: Tissue and Cell Preparationmentioning
confidence: 99%
“…We found that ND2 was present in the PSD fraction, and we estimated the amount of ND2 in this fraction was Ϸ15% of that in total brain homogenate. In contrast to ND2, neither the oxidoreductase protein ND4, another mitochondrially encoded component of complex I (25)(26)(27), nor Cyto1, an inner mitochondrial membrane protein component of complex IV (30), was detectable in the PSD fraction. Conversely, Cyto1 and ND4, as well as ND2, were readily detected in proteins from brain mitochondria (Fig.…”
Section: Nd2 Is Present In Psds In Brainmentioning
confidence: 82%
“…Mouse monoclonal antibodies to the flavoprotein (clone 2E3-GC12-FB2-AE2) and iron-sulfur protein (clone 21A11-AE7) of complex II, the core 2 protein of complex III (clone 13G12-AF12-BB11), subunits I (clone 1D6-E1-A8), II (clone 12C4-F12), III (clone DA5), IV (clone 10G8-C12-D12), Va (clone 6E9-B12-D12), Vb (clone 16H12-H9), and VIc (clone 3G5-F7-G3) of complex IV, and subunit ␣ of complex V (clone 7H10-BD4) have been described elsewhere (Marusich et al, 1997;Rahman et al, 1999;Taanman and Capaldi, 1993;Taanman et al, 1996). In addition, a mouse monoclonal antibody directed against the 39-kd subunit of complex I (clone: 20C11-B11-B11) was used.…”
Section: Immunological Analysismentioning
confidence: 99%